2008
DOI: 10.1038/leu.2008.236
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant signal transduction pathways in myeloproliferative neoplasms

Abstract: The BCR-ABL-negative myeloproliferative neoplasms (MPNs), polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF), entered the spotlight in 2005 when the unique somatic acquired JAK2 V617F mutation was described in 495% of PV and in 50% of ET and PMF patients. For the very rare PV patients who do not harbor the JAK2 V617F mutation, exon 12 JAK2 mutants were discovered also to result in activated forms of JAK2. A minority of ET and PMF patients harbor mutations that constitutively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 152 publications
(168 reference statements)
0
57
0
1
Order By: Relevance
“…These findings show that STAT3 serine phosphorylation is mainly involved in enhancing LAP expression in Jak2 V617F signalling pathways. JAK2 V617F mutation occurs at the HSC level (Jamieson et al, 2006;Kota et al, 2008). It is still unclear how this common mutation can induce three distinct MPN.…”
Section: Discussionmentioning
confidence: 99%
“…These findings show that STAT3 serine phosphorylation is mainly involved in enhancing LAP expression in Jak2 V617F signalling pathways. JAK2 V617F mutation occurs at the HSC level (Jamieson et al, 2006;Kota et al, 2008). It is still unclear how this common mutation can induce three distinct MPN.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic cells of ∆Hmga2 mice also showed high expressions of Jak2 mRNA and phosphorylated Stat3 or Akt 29) , suggesting that constitutive JAK2 -STAT3 and AKT activations induced by overexpression of HMGA2 may play a role in proliferative hematopoiesis. Although it should be investigated in the future how the expression of HMGA2 correlates with these pathways, it might contribute to activation of some signaling pathways shown in hematopoietic cells even without JAK2 mutation of some MPN patients 30) . Interestingly, it has been reported that HMGA2 upregulation was more apparent in JAK2V617F + than JAK2V617F − cases in PMF 25) .…”
Section: Discussionmentioning
confidence: 99%
“…JAK2V617F + hematopoietic cells fail to repopulate in competitive repopulation assays using some JAK2V617F knockin model animals 16,17) and in a coincidental human hematopoietic stem cell transplantation from JAK2V617F + idiopathic portal hypertension patient to a patient with MDS 39) . Moreover, even without a mutation in JAK2, MPL, or other signaling -related genes, a signaling involving JAK -STAT pathway are generally activated in MPN hematopoiesis, in which the cause of signaling activation is largely unknown 30,40,41) . Indeed, erythropoietin -independent erythroid colony formation from progenitor cells with only wild -type JAK2 has been shown 42) .…”
Section: Mutations In Cytokine Signaling -Related Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most work has been described in cell lines or in animal model systems, in which JAK2 and MPL mutations activate the STAT5, STAT3, PI-3K/AKT, and RAS-MAPK-ERK pathways. 4,8,9 However, these model systems may not adequately reflect the cellular context or the molecular complexity of human MPNs. In addition, where patient material has been used, technical aspects, such as the use of intervening in vitro culture conditions that do not reflect the proper in vivo milieu or the analysis of highly heterogeneous populations of cells using Western blotting or immunohistochemistry of fixed trephine sections, may limit the interpretation of these experiments.…”
Section: Introductionmentioning
confidence: 99%